Evidence for a decline in the population density of Antarctic krill Euphausia superba still stands. A comment on Cox et al. Issue 3 (25th April 2019) - Hill, Simeon L; Atkinson, Angus; Pakhomov, Evgeny A; Siegel, Volker
Abstract: Antarctic krill ( Euphausia superba  Dana, 1850 ) exemplifies the key role of marine crustaceans in fisheries, foodwebs, and biogeochemical cycles. Ecological understanding and policy decisions require information on population trends. We have therefore worked with international colleagues to publish KRILLBASE, a database of fishery-independent krill population information for every decade since the 1970s. These data were used by Cox et al. (2018) who dispute the evidence for a late twentieth-century decline in krill density (number per unit area) in the Southwest Atlantic sector of the Southern Ocean and claim to overturn "much of recent thinking about climate-driven change in krill populations." They support this claim with an analysis which reaffirms one non-significant result from an earlier paper but does not challenge the five significant results from that paper or those of other studies which support a decline. In this comment we examine the methods which led Cox and coauthors to conclude that krill density has been stable over the last 40 years. Although these authors provide a potentially useful approach, we show that their analysis was biased by the exclusion of usable net types, the inclusion of negatively biased data and down-weighting of high densities in the early part of the analysis period, the absence of recent data from the north of the sector, and a lack of statistical hypothesis testing. These factors maximise the chances of failure to detect a real decline. To aid future analyses we provide recommendations to supplement those which accompany KRILLBASE. We also suggest the need for consensus scientific advice on krill population dynamics based on agreed standards of evidence, evaluation of uncertainty, and a thorough understanding of the data. This will be more useful to policy makers and other stakeholders than polarised opinions. Meanwhile, the evidence for a decline in krill density still stands.